Examining the Role of Program Quality in Youth Sport Programming - Bean, Corliss (Université d'Ottawa / University of Ottawa, 2017)
The purpose of this doctoral dissertation was to examine the role of program quality within youth sport and understand the relationships between program quality, basic psychological needs support, and psychosocial development. Data were gathered from 33 youth programs across South Eastern Ontario using observations and corresponding field notes, self-report questionnaires from leaders and youth participants, and semi-structured interviews with leaders. The dissertation is composed of five articles. The first article uses structural equation modeling to examine the role of basic psychological needs support in mediating the relationship between program quality and psychosocial outcomes in the youth sport context. Results from this study indicate that both program quality and basic psychological needs play a role in facilitating psychosocial development; however, future research is needed to continue to understand this relationship. The second article presents findings from a sub-sample of the larger study in which a polynomial regression was conducted to examine discrepancies in program quality related to youth volleyball athletes’ needs support. Results indicated that discrepancies existed between researcher- and coach-perceptions of program quality and findings outline how this influences basic needs. The third article represents a mixed-methods examination of program quality and basic psychological needs support within two physical activity-based in-school mentoring programs. Findings from this study revealed a significant difference in program quality across the two programs, specifically related to psychological needs support. Program quality was found to significantly predict needs support within the girls’ program, but not in the boys’ program. Further, field notes were analyzed and practical strategies emerged that were found to help facilitate a quality mentoring program. The fourth article examined the importance of intentionally structuring the youth sport context to facilitate positive youth development across three types of youth programming. Results revealed that intentionally structured programs (both leadership and sport) scored higher on program quality and psychosocial outcomes than non-intentionally structured sport programs. In addition, intentional sport programs scored higher on some elements compared to intentionally structured leadership programs. Finally, the fifth article was a qualitative study that explored youth sport coaches’ perceptions of life skill development. Results indicated that coaches considered life skills to be important, yet believed they were a by-product of sport participation. Coaches also identified challenges associated with using an explicit approach to teaching life skills. Findings from this dissertation provide some of the first empirical accounts of examining program quality within youth sport and suggest that program quality plays an important role in fostering basic psychological needs support and psychosocial development. Moreover, the findings illustrate that there is a need for coach education related to how to structure the youth sport context in order to deliver a high quality program that facilitates psychosocial outcomes.
Keywords: Program Quality; Positive Youth Developement; Youth Sport; Mixed Methods; Life Skills